How Words Shape Our Thoughts: The Role of Connotation in Language - Eksaulina Simanjuntak; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study investigates the role of connotation in shaping meaning beyond the literal level in linguistic communication. Using a qualitative library research method, the analysis focuses on how connotative meanings influence emotional expression, social judgment, and cultural perception. The findings reveal that connotation operates dynamically through context whether interpersonal, cultural, or institutional significantly affecting how language is interpreted. Words with similar denotations may evoke entirely different responses depending on their connotative tone. For example, terms such as “thrifty” and “cheap” share core meanings but differ in emotional weight. Furthermore, connotation plays a powerful role in media, education, and political discourse. This underscores the necessity of connotative awareness for effective and ethical communication.